(3QSGdI aj JfLjS GdeJfLSs - (3CSO Gddg GdRfLGfjs
(3ChdgG (B:s
(3ChdgG(B: (3eSCdI(B: (3gd GdeJfLS fLS CedG? GdPj GSJbQ Ydjg GdaJhi ef Cgd GdYde Yh GdJfLjS eWdbG hdeG HdZ GdCeQ Edi GdcGTGfj bGd HCf ddfLS efMUQs
(3BNQgG (B:s
(3BNQgG(B: (3hJbhd Ef GdeJfLS GdLGa dG jfLS aj GdTQjYI GdeMeOjI haj GdCMcGe GdCdgjI GdeTJQcI Hjf GdQYjI hGdSdWGf hGdEeGe hGdfHjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis